Differential effects of Mediterranean vs. Western diets on coronary atherosclerosis and peripheral artery transcriptomics - Abusheikha, Aya Jamal; Johnson, Corbin S. C; Snyder-Mackler, Noah; Zimmerman, Kip D.; Negrey, Jacob D.; Chiou, Kenneth L.; Frye, Brett M.; Howard, Timothy D.; Shively, Carol A.; Register, Thomas C. (Frontiers in Nutrition, 2025)
Western diets and social subordination are associated with increased risk of cardiovascular disease. In this study, we investigated the impact of Western versus Mediterranean diets and social status on atherogenesis and arterial transcriptional profiles in a 30-month randomized study in middle-aged, cynomolgus monkeys (Macaca fascicularis). Atherosclerosis (intimal area) in the left anterior descending (LAD) coronary artery was higher in the Western diet group compared to the Mediterranean diet group (F = 5.25, p = 0.03). There was no effect of diet on intimal lesion size in the iliac and carotid arteries (p > 0.05). Diet altered the transcriptome in iliac arteries; at an FDR threshold of 0.05, seven transcripts were upregulated (WDR62, PKDCC, SLC29A2, MARS1, RAD21L1, MAMDC4, and ENSMFAG00000052859), and 13 transcripts were downregulated (PIK3R1, PABPC1, PAQR8, ZNF667, FGGY, EIF4B, ALDH3A2, ANP32A, KDM3B, XPO7, RPS20, TOMM20, and CHCHD7) in the Western compared to the Mediterranean diet cohort. These genes are associated with endothelial dysfunction, smooth muscle proliferation and migration, angiogenesis, and abnormal extracellular matrix (ECM) dynamics. In addition, two transcripts (ENSMFAG00000064154 [LncRNA] and ENSMFAG00000057515 [small nucleolar RNA U13]) were downregulated in subordinate monkeys relative to their dominant counterparts (FDR < 0.05). There was no effect of diet on the carotid artery transcriptome, but we did identify significant social status effects: Eleven transcripts were upregulated (KCNQ4, STIM1, TNKS1BP1, CSNK1D, INPPL1, PNPLA7, F10, RAD9A, KCNIP3, ENSMFAG00000059809 [LncRNA], and ENSMFAG00000053865 [secreted protein A0A7N9CS45]), and seven transcripts were downregulated (IRAK1BP1, KIAA0513, SMIM15, PSMD14, TOPORS, ARPC2, and ENSMFAG00000050714 [LncRNA]) in subordinate relative to dominant monkeys. These alterations were associated with dysregulated vascular tone and smooth muscle contractility, apoptosis, and abnormal ECM dynamics. These findings demonstrate differential effects of diet composition and social status depending on arterial sites. The effects of Western diet were observed primarily in the coronary and iliac arteries, whereas social status differences were observed primarily in the carotid arteries. Our results demonstrate that Western diets and social subordination have adverse, yet distinct and tissue-specific impacts on arterial atherogenesis and transcriptional profiles, highlighting the interplay between diet, social hierarchy, and vascular health.